Pengaruh E-Commerce Dan Word Of Mouth Marketing Terhadap Keputusan Pembelian Kopi ( Studi Pada Konsumen Produk Kopi PT Taman Delta Indonesiadi Kawasan Industri Terboyo Kota Semarang) - Muhammad Wifaqul Azmi; Abdul Kodir Djaelani; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract PT Taman Delta Indonesia is a company engaged in a comprehensive coffee business including coffee processing from private plantations, coffee bean marketing, and coffee export. PT Taman Delta Indonesia is located in the Terboyo industrial area of Semarang and is one of the leading green coffee exporters and coffee makers in Indonesia. This coffee company focuses on the quality of processing, roasting, and distributing its products. This study aims to determine and analyze the influence of E-Commerce and Word Of Mouth Marketing on the Purchase Decision of PT.Taman Delta Indonesia coffee.This study uses quantitative methods. The population in this study are consumers who have purchased the product and filled out the rating grade on the Tokopedia, Lazada and coffee shopee applications at PT Taman Delta Indonesia from October to November. The data collection technique is by distributing questionnaires. The sample of this research was taken by using purposive sampling technique with the Malhotra formula totaling 125 respondents to TdI coffee consumers. The variables in this study are E-Commerce (X1) Word Of Mouth (X2), and Purchase Decision (Y). The data analysis methods used are instrument test, normality test, classical assumption test, multiple linear regression analysis test hypothesis test, and test the coefficient of determination with the help of SPSS 20.0 software for windows.The results of this study indicate that 1.E-Commerce and Word Of Mouth Marketing Influence on Purchase Decisions 2.E-Commerce affect purchasing decisions. 3. Word Of Mouth Marketing has an effect on purchasing decisions. Keywords: E-Commerce, Word Of Mouth Marketing and Purchase Decision